Influence of Classroom Conduciveness on Students and Teachers’ attitude towards lessons’ attendance in Kwara South Senatorial District - Bello, M.B. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2020)
The study assessed the influence of classroom conduciveness on students' and teachers’ attitude towards lessons’ attendance in Senior School in Kwara South senatorial district. A descriptive form of survey design was adopted. The multistage sampling procedure was employed in sampling the respondents, which are the senior school II students and teachers from 33 public schools. One thousand one hundred and seventy-six students and teachers were proportionately sampled from 3,609. A – 10 items four-points-Likert scale Researchers’ designed questionnaire was adopted to elicit data, entitled “Teachers and Students Assessment of the Influence of Class Conduciveness on their Attitude towards lesson attendance (TSAICCATLA)”. The mean, standard deviation and z-test at 0.05 alpha level were used in the analysis of the data. The findings revealed that a classroom with poor physical structures of building, ceiling, ventilation, and lighting negatively affects both the teachers and students’ attitude and attendance to lessons. Likewise, Poor classroom facilities that is furniture and fan among others also constituted negative influence on teachers and students attitude to attendance to lessons and lastly, no significant difference existed in the assessment of both the teachers' and students' attitude towards lesson attendance in Kwara south senatorial district. It was classroom conduciveness which influenced students’ and teachers’ attitudes. Thus, it was recommended, that a school administrator should make classrooms conducive to facilitate effective teaching and learning.
Keywords: Conduciveness, Classroom, Attitude, Teaching, Attendance,Facilities